KEBIJAKAN PHYSICAL DISTANCING TERHADAP KECEMASAN MAHASISWA: STUDI CROSS-SECTIONAL: PHYSICAL DISTANCE POLICY ON UNDERGRADUATE STUDENT ANXIETY: A CROSS-SECTIONAL STUDY - Bela Yuli Selfia; Jayanti Dian Eka Sari; Xindy Imey Pratiwi; Ianatul Ulya Dewi (Journal of Community Mental Health and Public Policy, 2022)
ABSTRACTSustaining implementation of physical distancing including in the educational field is one of the policies to prevent Covid-19 confirmed cases in Indonesia. This policy can hinder undergraduate students' study needs and makes them feel anxious when they have to carry out online learning activities in long term. So, this study was conducted to determine the effect of physical distancing on the level of undergraduate students’ anxiety in East Java. This was an analytic observational study that used a cross-sectional and was carried out from May to July 2020. The sample in this study was 385 people who were taken using the accidental sampling method. The results showed that most undergraduate students in East Java feel very affected by the physical distancing policy with the majority of respondents feeling a mild level of anxiety as many as 157 people or 40.8%. Based on the simple linear regression test obtained the value of sig. 0.001 < 0.05 this indicates that the application of physical distancing has an effect on the level of undergraduate student anxiety during the Covid-19 pandemic. These results can be used as a basis for making future policies regarding anxiety in a pandemic situation.ABSTRAKProgram Pendidikan Jarak Jauh merupakan penerapan physical distancing di bidang pendidikan sebagai kebijakan pemerintah untuk mencegah penyebaran Covid-19 di Indonesia. Kebijakan ini dapat menghambat kebutuhan studi mahasiswa S1 dan membuat mereka merasa cemas ketika harus melakukan kegiatan pembelajaran daring dalam jangka panjang. Maka, penelitian ini dilakukan untuk mengetahui pengaruh physical distancing terhadap tingkat kecemasan mahasiswa S1 di Jawa Timur. Penelitian ini merupakan penelitian observasional analitik dengan metode cross sectional dan dilaksanakan pada bulan Mei sampai Juli 2020. Sampel dalam penelitian ini adalah 385 orang yang diambil dengan menggunakan metode accidental sampling. Hasil penelitian menunjukkan sebagian besar mahasiswa S1 di Jawa Timur merasa sangat dipengaruhi oleh kebijakan jaga jarak fisik dengan mayoritas responden merasakan tingkat kecemasan yang rendah diukur menggunakan kuesioner baku Zung Self-rating Anxiety Scale. Berdasarkan uji regresi linier sederhana diperoleh nilai sig. 0,001 < 0,05 yang berarti bahwa penerapan physical distancing berpengaruh terhadap tingkat kecemasan mahasiswa S1 selama masa pandemi Covid-19. Hasil ini dapat digunakan sebagai dasar untuk membuat kebijakan masa depan terkait kecemasan dalam situasi pandemi.